Analisis Persediaan Bahan Baku Menggunakan Metode Material Requirement Planning (MRP) pada CV. XYZ - Ahzam, Muhammad; Sulistyowati, Enik (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Raw material inventory is an important factor that influences company profits. CV. XYZ is a company engaged in the production of precast concrete. This company has not implemented special methods in planning and scheduling production. So far, companies have only relied on predictions of consumer needs without proper analysis, so they often experience excesses or shortages of raw materials. This research aims to determine the optimal amount of raw material inventory using the Material Requirement Planning (MRP) method. Data collection techniques include interviews, literature study, observations and observations. Calculations are carried out using the lot sizing method to determine the quantity and frequency of orders as well as total inventory costs. The analysis results show that the MRP method using the Periodic Order Quantity (POQ) technique produces lower total costs compared to Economic Order Quantity (EOQ). By applying the MRP method with the POQ technique, companies can optimize raw material inventory and minimize total inventory costs